Dinamika Keberagamaan pada Fase Usia Lanjut (Pusat Riset dan Inovasi Nasional, 2026)
This study is motivated by the context of religiosity in later life, which is characterized by various forms of decline, both emotional and spiritual, that may hinder the religious practices of older adults. The study aims to examine the condition of religiosity in the elderly phase. The main focus of this research is to explore and analyze the definition of old age, the characteristics of religiosity in later life, to identify religious problems commonly experienced by the elderly, and to examine the well-being of religious life during old age. This study employs a qualitative research method using a library research approach. The findings indicate that various challenges encountered in old age, such as anxiety, fear of death, and other psychological pressures, can be addressed through religious practices. Acts of worship, prayer, and spiritual reflection are able to provide inner peace, enhance the meaning of life, foster social harmony, cultivate acceptance of life’s realities, and help older adults respond to challenges in accordance with contemporary developments.